Brain-Derived Neurotrophic Factor (BDNF) protein levels in anxiety disorders: systematic review and meta-regression analysis - Suliman, Sharain; Hemmings, Sian M.; Seedat, Soraya (Frontiers in Integrative Neuroscience, 2013)
Background: Brain-Derived Neurotrophic Factor (BDNF) is a neurotrophin that is involved in the synaptic plasticity and survival of neurons. BDNF is believed to be involved in the pathogenesis of several neuropsychiatric disorders. As findings of BDNF levels in the anxiety disorders have been inconsistent, we undertook to conduct a systematic review and meta-analysis of studies that assessed BDNF protein levels in anxiety disorders. Methods: We conducted the review using electronic databases and searched reference lists of relevant articles for any further studies. Studies that measured BDNF protein levels in any anxiety disorder and compared these to a control group were included. Effect sizes of the differences in BDNF levels between anxiety disorder and control groups were calculated. Results: Eight studies with a total of 1179 participants were included. Initial findings suggested that BDNF levels were lower in individuals with any anxiety disorder compared to those without (Standard Mean Difference [SMD]=-0.94 [-1.75, -0.12], p≤0.05). This, however, differed with regards to source of BDNF protein (plasma: SMD=-1.31 [-1.69, -0.92], p≤0.01; serum: SMD=-1.06 [-2.27, 0.16], p≥0.01) and type of anxiety disorder (PTSD: SMD=-0.05 [-1.66, 1.75], p≥0.01; OCD: SMD=-2.33 [-4.21, -0.45], p≤0.01). Conclusion: Although BDNF levels appear to be reduced in individuals with an anxiety disorder, this is not consistent across the various anxiety disorders and may largely be explained by the significantly lowered BDNF levels found in OCD. Results further appear to be mediated by differences in sampling methods. Findings are, however, limited by the lack of research in this area, and given the potential for BDNF as a biomarker of anxiety disorders it would be useful to clarify the relationship further.